Influencia del sistema web en los procesos de trámite documentarios en la escuela de postgrado UNAP 2024 - Rios Carbajal, Jules Joao (2025)
The present thesis research, entitled "Influence of the Web System on Document Processing at the UNAP Graduate School 2024," set as its main objective: to determine the influence of a web-based system on document processing at the UNAP Graduate School in 2024. To this end, it was determined to determine the influence of document search time and response time. A quantitative approach with a non-experimental correlational design was used, using observation sheets applied to 20 office workers. The results confirmed the influence of the web system on the document processing at the graduate unit, since after the implementation of the web system, search time was reduced from 4.6 to 1.5 minutes, document tracking time went from 7.5 to 1.6 minutes, and response time decreased from 96 to 9 days. It was concluded that the web system influences the management of the documentary process.